Peningkatan Kesadaran Masyarakat Desa Jembatan Kembar-Lombok Barat Melalui Sosialisasi Mitigasi Bencana Banjir Berbasis Kolaborasi Dengan Badan Penganggulangan Bencana Daerah - Kencanawati, Ni Nyoman; Ihtiar, Rizky Alfatihatul; Amanda, Humami Syifa; Azra, Willy; Syawlina, Danisa; Nurin, Iffah Fikriana Al Nurin4 (Universitas Mataram, 2024)
Jembatan Kembar Village is located in Lembar District, West Lombok Regency, and is one of several villages often hit by floods during the rainy season. One of the problems in Jembatan Kembar Village related to disasters is the village community's lack of knowledge regarding disaster-prone conditions. For this reason, actions are needed that can increase community knowledge regarding disaster-prone conditions in the village. One form of activity that can be carried out is disaster response socialization activities. The socialization activity aims to provide an overview to the community regarding disaster-prone conditions in Jembatan Kembar Village and to increase community knowledge regarding actions that need to be taken to minimize the risk of disasters that can occur. The implementation of disaster response socialization activities is carried out in collaboration with the West Lombok Regional Disaster Management Agency (BPBD). The socialization activity was carried out after going through several stages starting from preparation, and establishing cooperation with implementing partners, namely the West Lombok BPBD, to the implementation of the socialization activity. In the socialization activity attended by a total of 34 people, information was obtained regarding what factors can trigger floods, both non-natural factors (humans) and natural factors. This socialization activity has an impact on increasing public understanding of disaster prevention measures, namely 12 actions that can be handled to minimize the risk of disaster before a flood occurs, 6 actions that can be conducted when a flood occurs, and 8 actions that at least need to be taken after a flood occurs.